Analysis of thalassemia syndromes and abnormal hemoglobins in patients from the Aegean region of Turkey - İrken, Gülersu and Ören, Hale and Ündar, Bülent and Duman, Murat and Gülen, Hüseyin and Uçar, Canan and Şanlı, Namık (The Turkish Journal of Pediatrics, 2002)
Turkey is located in a geographic area of the world where thalassemia syndromes and abnormal hemoglobins are common. In this study we aimed to evaluate the thalassemia syndromes and abnormal hemoglobins in patients from the Aegean region of Turkey. Among the patients admitted to our Pediatric Hematology or Hematology Clinic between January 1997-September 1999, hemoglobin electrophoresis of 3,228 cases investigated for anemia was done using high performance liquid chromatography. Beta thalassemia trait was diagnosed in 21.1%, beta thalassemia major in 0.2%, S-beta_thalassemia in 0.37%, Hb D in 0.37%, Hb S trait in 0.32%, Hb E in 0.18%, Hb O-Arab in 0.12%, Hb G-Copenhagen in 0.09%, Hb D-Iran in 0.06%, Hb Lepore in 0.06%, Hb Hasharon in 0.03%. Our results demonstrate that people in the Aegean region of Turkey have a wide spectrum of thalassemia syndromes and abnormal hemoglobins.